Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Celebrity Endorsment Terhadap Keputusan Pembelian (Studi Kasus Pada Jajanan Lumpur Arab Legenda Di Kota Malang) - Alfi Arifin; Muhammad Ridwan Basalamah; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to identify and evaluate how the Legend of Mud Arab Snacks in Malang's purchasing decisions are simultaneously and partially influenced by Product Quality, Service Quality, and Celebrity Endorsements. Purchase Decision is the dependent variable being measured, while Product Quality, Service Quality, and Celebrity Endorsement are the independent variables. Quantitative research using a descriptive methodology is the sort of research used in this study. From the beginning to the formulation of the study design, the quantitative research method's specifications are systematic, planned, and clearly defined. The SPSS program is used to manage data using multiple linear regression analysis. The information used includes both primary and secondary data that were gathered through direct observation, questionnaires, and interviewing methods. Because the sample size for this study is uncertain, we used Ferdinand's formula with the details of 20 indicators x 3 = 60. The analysis of the data revealed that the factors Product Quality, Service Quality, and Celebrity Endorsement simultaneously and partially influenced consumer choices at Jajanan Lumpur Arab Legend of Malang. Keywords : Purchase Decision, Product Quality, Service Quality, and Celebrity Endorsement